Involving University Students in Intercultural Communicative Competence Activities through the Use of Cultural Products and Practices (2017)
This document presents the findings of a research study developed with elementary level of English students from Instituto Internacional de Idiomas at Universidad Pedagógica y Tecnológica de Colombia. A series of pedagogical interventions were designed, in response to an initial diagnostic, which explored students’ Intercultural Communicative Competence (ICC) taking as referent Byram’s model (1997). Using the framework of qualitative action research, class activities, reflective journals and focus groups interviews were used to obtain the necessary information in order to reflect upon what students expressed regarding the ICC. The study revealed three categories: cultural recognition, cultural experience and cultural reaction.  Moreover, the results indicated that students were in an early stage of their ICC which was fostered through class activities. They understood the purpose and usefulness of the ICC. In addition, they were open and interested in including culture and ICC activities in the EFL classroom.